Critical Thinking and Creative Pedagogies in the Classroom - Naiditch, Fernando; dos Santos, Bettina Steren (INTERFACES DA EDUCAÇÃO, 2020)
The article discusses the meanings and the roles of critical thinking in the classroom. We start by placing the concept within the progressive pedagogical movement, which is rooted in the idea of learning by doing. Experiential learning is at the core of this kind of pedagogy and the belief is that students can only truly learn by engaging with the curriculum in an active and meaningful manner. Developing critical thinking is the goal of any educational system, particularly in democratic nations that understand schooling as a way of socializing children into the life of society as productive citizens. Although there seems to be an agreement in the importance of critical thinking in schools, teachers still find it difficult to develop practical classroom lessons and instructional strategies that develop higher order thinking skills. We discuss inquiry and project-based learning as well as Freire’s problem-posing approach as pedagogical instructional tools that can be used in the classroom to help students develop critical thinking. What do you want to do ? New mail Copy What do you want to do ? New mail Copy